2018
DOI: 10.1080/09168451.2017.1413325
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of carnosine-induced activation of neuronal cells

Abstract: Carnosine (β-Ala-l-His), an imidazole dipeptide, is known to have many functions. Recently, we demonstrated in a double-blind randomized controlled trial that carnosine is capable of preserving cognitive function in elderly people. In the current study, we assessed the ability of carnosine to activate the brain, and we tried to clarify the molecular mechanisms behind this activation. Our results demonstrate that carnosine permeates the blood brain barrier and activates glial cells within the brain, causing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Zinc deficiency induces depression, irritability, and mood lability, 60 with zinc supplementation improving these symptoms. l -Carnosine induces glial cells to secrete neurotrophins that activate neuronal cells, 61 and can inhibit monoamine oxidase in the brain, 62 indicating its potential for mood improvement. l -Carnosine also ameliorates amygdaloid-kindled seizures via its histaminergic action, 63 which could be beneficial for inhibiting trauma-related fear memory that occurs in binge eating patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency induces depression, irritability, and mood lability, 60 with zinc supplementation improving these symptoms. l -Carnosine induces glial cells to secrete neurotrophins that activate neuronal cells, 61 and can inhibit monoamine oxidase in the brain, 62 indicating its potential for mood improvement. l -Carnosine also ameliorates amygdaloid-kindled seizures via its histaminergic action, 63 which could be beneficial for inhibiting trauma-related fear memory that occurs in binge eating patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Yamashita et al . () demonstrated that carnosine permeates the BBB and activates glial cells within the brain, causing them to secrete neurotrophins such as BDNF and NGF.…”
Section: Food Protein‐derived Peptides For Preventing Cognitive Declinementioning
confidence: 97%
“…Further evidence suggests that carnosine functions as a molecular chaperone and as an inducer of antioxidant systems in oxidative stress conditions (Bellia et al, 2015). Interestingly, Yamashita et al (2018) demonstrated that carnosine permeates the BBB and activates glial cells within the brain, causing them to secrete neurotrophins such as BDNF and NGF.…”
Section: Healthy Cognitive Function Cognitive Declinementioning
confidence: 99%
“…Moreover, carnosine has anti-oxidative capacity against agents increasing ROS [28]. Another neuroprotective action of carnosine includes its attenuation of neurotoxicity induced by NMDA [29], beta amyloid, and inducible nitric oxide synthase [30] as well as increased trophic factors expression [31] (Figure 1). The effects of carnosine were reversed by inhibiting histidine decarboxylase (HDC) as well as histamine H 1 and H 3 antagonists, which suggests that carnosine’s neuroprotective mechanisms include not only the carnosine-histidine-histamine pathway, but also H 1 and H 3 receptors [29].…”
Section: Proposed Mechanisms Mediating the Role Of Carnosine In Thmentioning
confidence: 99%